Predictive Factors of Chronic Kidney Disease in Patients with Diabetes Mellitus at Sisaket Province - Silarak, Tawee; Piyabunditkul, Luckawee; kittipichai, Wirin (Journal of Research in Nursing-Midwifery and Health Sciences, 2020)
This study is a retrospective case control study aimed to analyze factors predicting the occurrence of chronic kidney disease in diabetic patients in Sisaket province. The sample included 311 diabetic patients with chronic kidney disease stage 3 and 622 diabetic patients without chronic kidney disease. Data collection was performed by interview and review medical record which was validated for content validity by 5 experts. It’s content validity index (CVI) is .80, Data were analyzed by descriptive statistics and logistic regression analysis. The results of binary logistic regression analysis showed that the factors significantly predicted the chronic kidney disease occurrence included non-steroidal anti-inflammatory drug use (OR = 4.28), salty food consumption (OR = 3.54), exercise and sports activities (OR = 3.03), the quantity of drinking water (OR = 3.00), herbal drug use (OR = 2.66), blood glucose control (OR = 2.51), hypertension (OR = 2.43), systolic blood pressure (OR = 2.22), urinary tract stones (OR = 2.11), sweet food consumption (OR = 2.12), family history of chronic kidney disease (OR = 1.94), high fat dietary (OR = 1.71) and smoking (OR = 1.55). Knowing factors predicting the occurrence of chronic kidney disease would help diabetic patients to know their risks and be useful for health care provider to develop health service plans in order to prevent the deterioration of the kidney function